2012
DOI: 10.1152/ajpregu.00068.2012
|View full text |Cite
|
Sign up to set email alerts
|

Leptin signaling in the nucleus of the solitary tract alters the cardiovascular responses to activation of the chemoreceptor reflex

Abstract: Circulating levels of leptin are elevated in individuals suffering from chronic intermittent hypoxia (CIH). Systemic and central administration of leptin elicits increases in sympathetic nervous activity (SNA), arterial pressure (AP), and heart rate (HR), and it attenuates the baroreceptor reflex, cardiovascular responses that are similar to those observed during CIH as a result of activation of chemoreceptors by the systemic hypoxia. Therefore, experiments were done in anesthetized Wistar rats to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 78 publications
3
14
1
1
Order By: Relevance
“…Similar transient depressor responses to angiotensin II injection within the NTS have been observed, in part due to glutamate and substance P release (12,16). While our collective findings suggest that leptin does not play a role in modulation of cardiac vagal chemosensitive fibers, this hormone has been shown to modulate neuronal circuits within the NTS controlling respi- ratory and cardiovascular responses to arterial chemoreflex activation (9,19). Endogenous leptin tone for baroreflex suppression during aging.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Similar transient depressor responses to angiotensin II injection within the NTS have been observed, in part due to glutamate and substance P release (12,16). While our collective findings suggest that leptin does not play a role in modulation of cardiac vagal chemosensitive fibers, this hormone has been shown to modulate neuronal circuits within the NTS controlling respi- ratory and cardiovascular responses to arterial chemoreflex activation (9,19). Endogenous leptin tone for baroreflex suppression during aging.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, higher doses of leptin within the NTS can evoke pressor and sympathoexcitatory responses in younger rats (9,29). The finding that leptin transiently decreased blood pressure in older SD rats, an action not seen in the younger rats in the previous study, may suggest that the neural pathways activated by exogenous leptin within the NTS are altered with aging.…”
Section: Discussionmentioning
confidence: 60%
“…Reduction in synaptophysin has been reported in a number of central sites under pathophysiological conditions [42,49]. Although leptin does not appear to be involved in the reduction in synaptophysin during exposure to IH, leptin does play an important role in mediating chemoreceptor reflex responses as injections of leptin into the caudal medial NTS potentiates the cardiovascular and sympathetic reflex responses to activation of the chemoreceptor reflex [11]. Furthermore, the response of NTS neurons to chemoreceptor reflex activation has been shown to be facilitated by leptin [12].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in circulatory levels of leptin have been reported to not only exacerbate the effects of chemoreceptor reflex activation on the cardiovascular system, but also potentiate the neuronal responses in NTS to chemoreflex activation [12] while inhibiting the neuronal responses to baroreflex activation [9]. These affects are not observed in leptin receptor deficient Zucker obese rats [9,11]. Additionally, administration of leptin directly into the caudal medial NTS of Sprague-Dawley rats potentiated the cardiovascular and sympathetic responses to activation of the chemoreceptor reflex [10].…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, several studies have reported that systemic administration of leptin increases the expression of the c-fos gene within caudal NTS (Elmquist et al, 1997(Elmquist et al, , 1998Elias et al, 2000;Grill et al, 2002), regions that are known to receive cardiovascular afferent projections (Ciriello, 1983;Erickson and Millhorn, 1991;Finley and Katz, 1992;Mifflin, 1992;Chitravanshi et al, 1994;Ciriello et al, 1994;Chitravanshi and Sapru, 1995;Spyer et al, 1997;Dampney et al, 2003;Spyer and Gourine, 2009). In addition, administration of leptin into the caudal NTS has been reported to elicit increases in arterial pressure and renal sympathetic nerve activity (Mark et al, 2009;Ciriello and Moreau, 2012). Furthermore, leptin injections into the NTS have been shown to attenuate the cardiovagal component of the baroreceptor reflex (Arnold et al, 2009), while potentiating the sympathoexcitatory responses to activation of the chemoreflex .…”
Section: Introductionmentioning
confidence: 99%